Loneliness, social support and lifestyles in gay and heterosexual women : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Psychology at Massey University - Johnson, Janet (Massey University, 1990)
Lifestyle, social support and loneliness in gay women have been poorly documented. Further to this no comparisons have been made with heterosexual women in these areas. The present investigation assessed lifestyle, social support and loneliness and involved two samples, 87 heterosexual women and 63 homosexual women. Of particular interest in the area of social support was support offered by family and friends, as perceived by the respondents. Lifestyle variables were studied to possibly offer an explanation if any differences were found between the two groups. Loneliness was assessed as a multidimensional construct involving four types of relational deficits. Finally variables predicting loneliness were explored. Results indicated that the gay women suffer relationship deficits in the areas of family and community. They also perceived less support from the family than the heterosexual women, and had less kin in their support network, relying on friends more in times of need. This may be because friends of the gay women, both heterosexual and homosexual, tended to react more positively than parents, to finding out about their lesbianism. The variables of perceived support were the main predictors of family and friends loneliness in heterosexual women. These and variables associated with lesbianism, such as feelings of isolation and who was first told, were found to be the best predictors of the different areas of loneliness in gay women. The results suggest that gay women have become alienated from their families and society in general.
Keywords: Social conditions; Lesbians; Sociological aspects; Women; Lifestyles